Soil properties and storage of organic carbon in the land use pasture and forest - Barrezueta-Unda, Salomón Alejandro; Velepucha-Cuenca, Kelvin Adrián; Hurtado-Flores, Luis; Jaramillo-Aguilar, Edwin Edison (Revista de Ciencias Agrícolas, 2019)
Soil is probably one of the natural resources most vulnerable to climate change. Composes most of the carbon stock in terrestrial ecosystems. The aims of this study were: to characterize the use of pastureland and native forest in two sites in El Oro province (Ecuador), based on their physical, chemical, and biological properties, and to compare the Soil Organic Carbon (SOC) stock at three depths. For this purpose, plots were established in Brachiaria sp pastures and native forests in the coastal area of Machala, Santa Inés site (SI), and the mountains of Chilla, Cune site (CN). Soil sampling was done at three depths (C1=0-10cm; C2=10-20cm; C3= 20-3 cm). The SI soils showed significance (p-value<0,05) among the stored SOC layers. The highest stored SOC value was for SI forest (C1, 36,30megagrams-Mg C ha-1), in an alkaline pH and clay loam texture. In CN soils, stored COS revealed no significance between layers, and values ranged from 27,64Mg ha-1(C1, CNforest) to 35,01 Mg C ha-1 (C3, CNpasture), in an acidic pH, sandy loam texture and high levels of Fe (761,71-938,34 mg kg-1). Soil properties play an important role in stored SOC levels; therefore, sequestration of SOC must be considered to develop optimal pasture management.